PENETRASI ADAT BATAK ANGKOLA TERHADAP HUKUM ISLAM DI KECAMATAN BATANG ANGKOLA - Nasution, Muhammad Arsad (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2015)
Custum has influence the Islamic Law ecpecialy related to merriage law.Â  Key points where customary law, including the law of Islam is at the event making a proposal, the party walimah and household peorses dispute resolution in this case a husband and wife. Thus the intersection between customary law and Islamic law can be obtained in the process of grounding the Islamic law. Islamic law can not be earthed directly without a device equipped with the customary law. Attitude contradicting Islamic law with customary law as a whole will make Islamic law looks stiff and coused adherents have a narrow view of making it easier for the fire hostility.